Enhanced antibacterial activity of magnetic biochar conjugated quaternary phosphonium salt. (15th August 2020) - Fu, Yuhao; Wang, Fang; Sheng, Hongjie; Xu, Min; Liang, Ying; Bian, Yongrong; Hashsham, Syed A.; Jiang, Xin; Tiedje, James M.
Abstract: Microbial contamination in water remains a global issue in threatening human health. Although current disinfection methods can effectively control microbial contamination, the formation of harmful disinfection byproducts is increasingly questioned. Towards this goal, a facile, green and low-priced bacteriocide - magnetic biochar/quaternary phosphonium salt (MBQ) - was developed using precipitation of iron oxide on biochar followed by ion exchange with quaternary phosphonium salt (QPS). Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus - were used as model pathogens to quantify the antibacterial activity and to elucidate the antibacterial mechanism. MBQ was an effective antimicrobial agent against both pathogenic bacteria. The controllable release of QPS and magnetic recovery of MBQ favored antibacterial reuse. Significant disruption of membrane led to the inactivation of bacteria, resulting from the loss of cell membrane integrity and permeability. The induced oxidative damage inhibited the essential cell metabolism. Penetration of MBQ nanoparticles through the cell wall and membrane into the cytoplasm enhanced the biocide effect. Taken together, MBQ, presenting effective, recyclable and long-acting antibacterial properties, has a promising application in bacterial decontamination. Graphical abstract: Image 1 Highlights: Magnetic biochar conjugated with quaternary phosphonium salt (MBQ) is synthesized. MBQ is an effective bactericide against Gram-negative and Gram-positive pathogens. MBQ with a long-term antibacterial property is quickly recoverable allowing reuse. The induced oxidative stress and germicidal agent QPS intensify the cell damage. Penetration of MBQ nanoparticles into the cytoplasm may enhance the biocide effect.